Classification of electric resistive heating boilers for autonomous water heating systems - A. L. Toropov (Vestnik MGSU)
Introduction. Electric boilers are considered as an important element of the energy transition from the use of hydrocarbon fuels to renewable energy. Electric boiler is one of the popular solutions of “Power-to-Heat” technology, widely used in households for heating with water systems with radiators and low-temperature heating devices of the “floor heating” type. The paper considers a variant of Joule heating of the coolant of heating systems, by means of which heat is released when an electric current passes through a conductive element.Materials and methods. The object of the research is the variants of designs of heat exchangers for generating heat energy using resistor heating elements of normal conductor and semiconductor type. Various variants of indirect heating of the coolant and contacts of the surface of the heating elements with the coolant are considered. Methods of comparative analysis and scoring of the applicability of various designs are used in the work.Results. The classification of electric boilers by types of heating resistors, by contact, by placement of heating elements in the heat exchanger, by the shape of the heat exchanger, by the variant heating element contact with the coolant is presented. A comparative comprehensive analysis of variants of electric heat generators is given.Conclusions. The results of comparative analysis of design variants of electric boilers show the prospectively of using semiconductor thermistors as heating elements. According to the design of the heat energy generation chamber in terms of compactness, power density and reduction of precipitation conditions for coolant stiffness, channel plate electric heat exchangers are the most effective.